Pendapat empat imam madzhab tentang wali nikah wanita - Bakar, Abu; Hannan, Abd; Mofid, Hazem (AS-SAKINAH, 2023)
The validity of female guardians is still a controversy in Islamic law. According to the majority of scholars of the Maliki, Shafi'i and Hambali Mazhabs, female guardians are not allowed in the sense that the marriage is invalida This type of thesis research is literature or (Library research), which is descriptive analysis. The data collection technique is documentation, namely by searching and collecting books and books, especially those related to the study of this problem. It is concluded that according to the Maliki, Shafi and Hambali Madhhabs, a guardian is required in a woman's marriage contract, while according to the Hanafi Madhhab, it is permissible not to have a guardian in a woman's marriage contract on the condition that the husband is suited and the dowry is in accordance with the surrounding community.